Plasma Cell Dyscrasias: Laboratory Diagnostic Approach and Differential Diagnosis - Noviana, Elvi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
A diverse spectrum of clonal disorders arising from terminally differentiated B cells that secrete monoclonal immunoglobulins or their components is collectively referred to plasma cell dyscrasias (PCDs). Clinical presentations vary widely, from early asymptomatic stages such as monoclonal gammopathy of undetermined significance, to organ-damaging conditions including multiple myeloma, AL amyloidosis, Waldenström macroglobulinemia, and other less common plasma cell related syndromes. Accurate laboratory diagnosis is essential because early recognition of monoclonal proteins can prevent irreversible organ damage involving bone, kidney, or hematopoietic systems. This review summarizes current laboratory diagnostic approaches for PCDs and discusses key differential diagnosis across major PCD entities. A narrative literature research was performed using open-access databases (PubMed, Scopus, ScienceDirect, and Google Scholar), focusing on publications from 2015-2025 addressing diagnostic modalities, disease-defining criteria, and distinguishing features relevant to clonal and reactive plasma cell processes. Findings highlight that optimal diagnosis relies on integrating serum and urine studies, immunofixation, serum free light chain assay with immunophenotyping, cytogenetic profiling, and bone marrow assessment. Flow cytometry enables clonal confirmation through aberrant plasma cell immunophenotypes, whereas FISH identifies recurrent genomic abnormalities with prognostic relevance. Molecular assays provide additional refinement in selected cases. Accurate interpretation requires correlation with clinical features to differentiate PCDs spectrum. A structured, multimodal diagnostic strategy is essential for precise classification, risk stratification, and guiding patient management across diverse healthcare settings.